2022
DOI: 10.3389/fbioe.2022.849441
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and In Vivo Toxicological Evaluation of Copper (II) Oxide Containing Herbometallic Siddha Nanocomplex “Thamira Parpam”

Abstract: “Thamira parpam” (TP), a copper-based herbometallic oxide (copper (II) oxide) nanodrug has been used in Siddha medicine for centuries because of its anti-ulcerogenic property. However, the physicochemical properties and in vivo toxicity of TP still remain elusive. Rigorous clinical translation requires deciphering these vital properties. We have synthesized TP following a gold standard protocol in the traditional Siddha methodology. We assessed the size, phase, elemental constituents, and thermal stability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…As a result, much emphasis is being placed on exploiting the production of CuONPs utilizing biological resources. Although there have been a few papers on the use of microbes and plant extracts for the synthesis of CuONPs [ 11 , 12 , 13 ]. Piper beetle and Piper Longum combined use have not been reported prior, and a review of the current literature revealed that this approach of CuONP synthesis has been less researched.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, much emphasis is being placed on exploiting the production of CuONPs utilizing biological resources. Although there have been a few papers on the use of microbes and plant extracts for the synthesis of CuONPs [ 11 , 12 , 13 ]. Piper beetle and Piper Longum combined use have not been reported prior, and a review of the current literature revealed that this approach of CuONP synthesis has been less researched.…”
Section: Introductionmentioning
confidence: 99%